Congenital Visceral Vascular Variation Causing Gastrointestinal Hemorrhage: A Case Report - Wei, Yingli; Ye, Zhiqiu; Shang, Ning; Yang, Chaoxiang; Liao, Minyan; Pan, Yunxiang (Frontiers in Pediatrics, 2021)
Variations in the visceral vasculature are often encountered, but rarely cause clinical symptoms. We report a 12-year-old girl with portal hypertension caused by congenital variations in visceral vessels. The clinical manifestations included gastrointestinal hemorrhage and ascites. The common hepatic artery and splenic artery stem shared the same trunk from the aorta, and the common hepatic artery was directly connected with the main portal vein to form an arteriovenous fistula. In addition, the left hepatic artery and the left gastric artery shared a common trunk termed the "hepatic-gastric trunk" which originated from the anterior wall of the aorta, while the right hepatic artery originated from the superior mesenteric artery and supplied the right liver. The patient was treated with interventional embolization and remained in good condition throughout the follow-up and at the time of publication.